The role of Government for developing digital platform to establish a freelancer’s market in Pakistan - Zarwish Bint E Ishaq; Hamza Akram (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2023)
This paper explores the perceptions of Pakistani freelancers regarding the role of the government in enhancing their career success. Through a qualitative approach by in-depth interview, the study examines the challenges faced by freelancers in Pakistan and the extent to which they believe government policies and initiatives can help address these challenges. Findings suggest that while freelancers face various obstacles, including lack of access to finance, limited opportunities, and inadequate infrastructure, they perceive the government's role as minimal. Participant expressed the need for greater recognition of the freelance industry, stronger regulatory frameworks, and more investment in skills development and digital infrastructure. The paper concludes that the Pakistani government must play a more active role in promoting and supporting the freelance industry, as it has the potential to contribute significantly to the country's economic growth and development